2010
DOI: 10.1590/s0103-50532010000100007
|View full text |Cite
|
Sign up to set email alerts
|

Eco-friendly synthesis of 2-substituted benzothiazoles catalyzed by cetyltrimethyl ammonium bromide (CTAB) in water

Abstract: Uma série de benzotiazóis 2-substituídos foi sintetizada pela condensação de 2-aminotiofenol com aldeídos (RCHO: R = Alquil, Aril, Heteroaril, 2-Arilformil) na presença de quantidade catalítica de brometo de cetiltrimetil amônio (CTAB) em água e sem adição de solventes orgânicos e oxidantes. Assim, usando esse protocolo, 2-alquilbenzotiazóis foram sintetizados em altos rendimentos e 2-arilformilbenzotiazóis foram obtidos pela condensação de 2-aminotiofenol com arilformil aldeídos pela primeira vez.A series of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…α-Keto acids bearing methyl and bromo groups were fully tolerated, providing the desired products 5bb and 5bh with 93 and 86% yields, respectively. Su reported that 2-substituted benzothiazoles were synthesized by the reaction of 2-aminothiophenol with aldehydes in water; however, 5 mol% cetyltrimethylammonium bromide should be added as a catalyst . Compared with Su′s method, here the reaction that proceeds in water under catalyst-free conditions is more green and sustainable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…α-Keto acids bearing methyl and bromo groups were fully tolerated, providing the desired products 5bb and 5bh with 93 and 86% yields, respectively. Su reported that 2-substituted benzothiazoles were synthesized by the reaction of 2-aminothiophenol with aldehydes in water; however, 5 mol% cetyltrimethylammonium bromide should be added as a catalyst . Compared with Su′s method, here the reaction that proceeds in water under catalyst-free conditions is more green and sustainable.…”
Section: Resultsmentioning
confidence: 99%
“…Typical Procedure for the Synthesis of 5-(2-Ethoxyphenyl)-1methyl-3-propyl-1H-pyrazolo [4,3-d]pyrimidin-7(6H)-one (13). To a test tube (1.8 cm × 18 cm) were added 2-(2-ethoxyphenyl)-2-oxoacetic acid 12 (0.3 mmol, 1.5 equiv) followed by 4-amino-1-methyl-3-propyl-1H-pyrazole-5-carboxamide 11 (0.2 mmol, 1.0 equiv) and H 2 O (1 mL).…”
Section: Scheme 3 Proposed Reaction Mechanismsmentioning
confidence: 99%
“…Also, the hydrophobic chain of SDS forms micelles in water, which can capsulate reactants in a tight place with a diameter of 10–28 Å for the reaction to occur (Scheme ). Moreover, these micelles in water increase the solubility of organic compounds in water …”
Section: Resultsmentioning
confidence: 99%
“…Synthesis of a third series of compounds 17 was performed as shown in thiazol-2-yl)phenol 15 25 was reacted with propargyl bromide 2 in the presence of K 2 CO 3 in DMF at 80 °C for 16 h to form 2-(4-(prop-2-yn-1-yloxy)phenyl) benzo[d]thiazole 16. A click reaction of 16 with an in situ prepared benzyl azide 6 gave the title compounds 17.…”
Section: Chemistrymentioning
confidence: 99%
“…Pure products 14 were obtained by recrystallisation from a mixture of ethanol and ethyl acetate. 25 in DMF. The mixture was stirred at 80 °C for at least 12 h. After completion of the reaction (monitored by TLC), the mixture was diluted with EtOAc (25 mL) and water (25 mL) and the organic layer was extracted with EtOAc (2 × 25 mL).…”
Section: Synthesis Of Compounds 14; General Proceduresmentioning
confidence: 99%